The role of the advanced practice nurses in the Philippines in the control of hypertension - Duller, Sarla F. (Manila College of Nursing, University of the Philippines Manila, 2017)
The death of human resources for health and inequitable distribution of health facilities in the Philippines were the same factors that led to the creation of the Advanced Practice Nurse (APN) role in the United States and other countries over five decades ago. This study was conducted to provide the requisite empirical data supporting the APN role enactment in the Philippines. A four-phase mixed methods study was conducted to demonstrate a model for APN in the country that is focused on the prevention and control of primary hypertension. A validated module was ised in the Hypertension Training Program for APNs to prepare a convenience sample of 24 masters-prepared nurses in providing entry-level APN care to patient with primary hypertension. Using a paired T-test, the knowledge and self-efficacy of the nurse participants were shown to statistically increase from pre-training to post-training (p<0.001). Three of these trained masters-prepared nurses provided APN-level care for patients in the APN-Led Hypertension Clinic, while closely collaborating with a physician. Eight hundred twenty-two (822) participants were screened in 21 barangays in District V of the City of Manila, and 317 satisfied the inclusion criteria. One hundred seven (107) participants signed the informed consent form, and 63 of these were randomized to be seen by either an APN or a primary care physician. A total of 45 patients completed the follow-up check-up (APN = 21, MD = 24). Using Mixed ANOVA, the within-subjects main effects revealed that the following outcomes improved from initial visit to follow-up visit after one month: systolic BP (p=.02), diastolic BP (p=.002), knowledge (p<.001), self-management ability (p<.001) and medication adherence (p=.021). The main effects for body mass index and patient satisfaction were not significant. The interaction effects for all these patient outcomes were not significant, indicating that patients in the APN group had statistically comparable outcomes compared to those in the MD group. Furthermore, those patients in the APN group had a statistically longer length of consultation (p=.01). Using Critical Incidents Technique, qualitative analysis of APNs narratives during the APN-Led Hypertension Clinic revealed that their experiences had significant positive contributions to the aim of the study. Overall, the training program showed excellent outcomes among the nurse participants, which were positively translated into the patient outcomes in the APN-Led Hypertension Clinic. These are empirical evidence of the effectiveness of the APN role enactment and its promising potentials in the Philippines.
Dissertation (Doctor of Philosophy in Nursing) -- University of the Philippines Manila, June 2017.
Bibliography: leaves 171-189.
Keywords: Hypertension -- Nursing -- Practice; Hypertension -- Control